Transition in Afghanistan hope, despair and the limits of statebuilding - Maley, William 1957- (Durham modern Middle East and Islamic world series, 2018)
This book, by one of the leading authorities on the subject, presents a deep analysis of the very difficult current situation in Afghanistan. Covering a wide range of important subjects including state-building, democracy, war, the rule of law and international relations, the book draws out two overarching key factors: the way in which the prevailing neopatrimonial political order, established in an earlier "state-free" period, has become entrenched, making it very difficult for any other political order to take root; and the hostile region in which Afghanistan is located, especially the way in which an ongoing "creeping invasion" from Pakistani territory has compromised the aspirations of both the Afghan government and its international backers to move the country to a more stable position